2000
DOI: 10.1080/096382800413970
|View full text |Cite
|
Sign up to set email alerts
|

Patient mood and carer strain during stroke rehabilitation in the community following early hospital discharge

Abstract: Carer stress and patients depression scores are related to the severity of stroke-related disability. Strategies to address patient mood and carer stress should be present in community services providing early stroke rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
0
26
1
Order By: Relevance
“…Either a stroke nurse or a social worker offered information or therapy in the community. Only four of these studies [12,21,23,25] found significant improvement for the caregiver. Dennis et al [12] evaluated a stroke family care worker, who tried to identify unmet needs and aimed at fulfilling these needs accordingly.…”
Section: Effects Of Type Of Interventionmentioning
confidence: 93%
See 1 more Smart Citation
“…Either a stroke nurse or a social worker offered information or therapy in the community. Only four of these studies [12,21,23,25] found significant improvement for the caregiver. Dennis et al [12] evaluated a stroke family care worker, who tried to identify unmet needs and aimed at fulfilling these needs accordingly.…”
Section: Effects Of Type Of Interventionmentioning
confidence: 93%
“…Of these 10 studies there was significant reduction of depression [12,17], improvement of knowledge [11,13,18,23,29] improvement in satisfaction with care [12], improvement in family functioning [13], improvement in quality of life [17,24,25], better problem solving skills [17,18], more social activities in daily life [13,25], more social support [13,18] and less burden [13,21].…”
Section: Outcomementioning
confidence: 99%
“…Improving patients' mood is also important because it may affect the patient-care partner relationship following discharge. 63 In a study of music and patients' mood that used a single subject design, Magee and Davidson 6 used the Profile of Mood States instrument in a cohort of 14 patients (4 with stroke, 5 with multiple sclerosis, and 5 with traumatic brain injury) and reported that composed-anxious, energetic-tired, and agreeablehostile mood states were significantly improved from before to after a music therapy intervention. Thus, it is reasonable to consider that music therapy may also help to maintain a positive outlook in other neurologically injured stroke patients who are undergoing rehabilitation therapy.…”
Section: Role Of Music In Stroke Rehabilitationmentioning
confidence: 99%
“…The BI correlates highly with motor ability and physical disability, 8,41,42 leaving cognitive and psychological consequences common to stroke as predictors of a poor outcome potentially neglected. 13,19,31 Furthermore, the BI and mRS have been shown to be inconsistent indicators of independence due to the lack of consensus between measures, 37,38 which calls into question the clinical and research utility of the BI and mRS to measure perceptions of disability, independence, and participation.…”
Section: 2628mentioning
confidence: 99%